Ø§Ù„Ø´Ù€Ù€Ù€Ù€Ù€Ù€Ù€Ø±ÙŠØ¹Ø© Ø¶Ø¯ Ø§Ù„Ø¥Ø¬Ù€Ù€Ù€Ù€ØªÙ…Ø§Ø¹Ù€Ù€Ù€Ù€Ù€Ù€Ù€ÙŠØ© Ø¹Ù„Ù‰ Ø§Ù„Ù‚Ù€Ù€Ù€Ù€Ù€Ù€Ù€Ù€Ù€ÙˆØ§Ø¹Ø¯ Ø§Ù„ÙÙ‚Ù€Ù€Ù€Ù€Ù€Ù€Ù€Ù€Ù€Ù€Ù€Ù‡ÙŠØ© PERKEMBANGAN HUKUM ISLAM VERSUS KEHIDUPAN SOSIAL DALAM PERSPEKTIF AL-QAWAID AL-FIQHIYAH - Muslimin, Ahmad (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
Allah as a judge, so law from god and if he as syaari’, so about the manner of Syari’ah is legal which is revealed allah contained in the Al-Qur’an and al-Hadits, definite and unchanged, law about the manner of ’ ah most general; put basic principles while al-fiqh is understanding law that is inferred of about the manner of Syari’ah to respond to certain situations who do not directly discussed in law about the manner of Syari’ah, al-Fiqh change according to the situation and condition in which applied, law al-fiqh tending to specific; shows how basic principles about the manner of Syari’ah to will be applied appropriate to the state of. But, although indeed meaning about the manner of Syari’ah and al-fiqh having the difference, but then translated loosely as islamic law. History shows how islamic law undergo development enough then the dynamic evolotif become one of the base of the established law. Many observers scholars and thinkers talk about ‘ ilm al-syari ’ ah, al-maqashid al-syari ’ ah or tujuan-tujuan the law all the goal is right, all the al-masalih simultaneously form a law applicative and fungsionil in the communities. In addition , as a product law in resolve the conflict in various forms , can be traced sources and bare her foundations of verse al-qur' s and al-hadits , because was certainly can defend al-maslahah .This is where the strategic position of al-qawaid al-fiqhiyah in search of the common ground between al-syari’ah with al-qawaid al-fiqhiyah .